Analysis of supply chain issues in a healthcare company - Kukkonen, Joonas (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
The aim of this thesis is to produce understanding of problems that supply chain management faces. The idea is to compare empirical data with previous literature. Researching supply chain management issues is meaningful because supply chain is key part in the today’s world. The research includes theoretical background and empirical research. In Discussion and conclusion chapter these two are compered. The idea is not to find generalizations, but to examine if the case company faces similar issues that others have faced. Theoretical background includes the concept of supply chain management, and the key components of supply chain management. Subsequently, it discusses about the key issues that supply chain management might face. The idea is to produce a view of supply chain management, and how it should be managed. Additionally, the idea is to present common issues it might face. However, this thesis concentrates on more strategical and organizational issues. This is a case study of a company, which is a global healthcare manufacturing corporation. Empirical data was collected by arranging 20 semi-structured interviews. The idea is to present the sup-problems by using Fishbone diagram, and how these influence on company’s supply chain management. The case company’s supply chain is complex and it is affected by many functions and individuals. It faces several issues. These issues are categorized to five groups: strict targets, lack of control over cost management, lack of co-operation, information management issues and ideological issues. The empirical results were similar to those that were presented in theoretical background. Subsequently, the strict targets were the main reason for many problems that the company faces. These affected company results both directly and indirectly. According to this thesis, the case company should redesign its targets. Further research could examine the influence that targets have in the company’s supply chain.